Aspects related to quality of life and physical activity of military police officers of Santa Catarina - Brazil - Antônio Melo Schlichting; Jader Peron Schlichting; Paulo José Barbosa Gutierres Filho; Fernando Adami; António Silva (Desafio Singular, 2012)
This study aims to investigate the relationship between quality of life, health, physical activity, occupation, body composition and sociodemographic characteristics of Military Police of Santa Catarina, Brazil. 302 Police Officers participated in this study, randomly selected through a simple drawing and in accordance with the eligibility criteria. Data were collected through two questionnaires from the World Health Organization, one of them concerning quality of life (WHOQOL-Bref), and the other, concerning physical activity (IPAQ-Long), and additionally, a worksheet containing sociodemographic, anthropometric, occupational and health-related variables. It was found that most of the Military Police is married, schooled, with an average of 36.6 years old and 15.1 years of the police action, has good perception for quality of life, has levels of physical activity above the recommended, has weight in the range recommended, and has good health. It can be concluded that there are associations of quality of life with leisure physical activities, height and marital status.